Use of Waste Tier in Construction of Bitumen Road - Yakub Ansari, Chhaya Chavan , Khalid Iqbal , M. Junaid,Abdullaha Khan (International Journal of Advanced Science and Technology, 2020)
This paper is based on the review study on waste tier generation, Its environmental problem, and its use in construction of the bitumen road. The growth rate of population which depend upon on vehicles is the backbone of economic development of any country. India is the second fast growing automobile industry in the world. In today’s era, solid waste management is the thrust area. On the other side, the traffic intensity is also increasing. As a result, amount of waste tires is also increasing. The increasing in producing of waste tire has created many problems such as increasing landfill space also leads to environmental pollution by producing CO2 which causing health hazards to living being. Parallel to this is tremendous increasing of roads construction as a result of heavy traffic on roads. This study reviews regarding the use of crumb rubber (waste tires in powder form) in bitumen using the wet process. The study focuses on the crumb rubber as a replacement to the total weight of bitumen. The design or life span for all highways and urban roads is 10 – 20 years.